Original paperDisease extent and severity in patients with atopic dermatitis and food allergy - Rosińska-Więckowicz, Anna; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction: Subjective incidence of symptoms of food allergy (FA) is very high among patients with atopic dermatitis (AD), yet standardized procedures rarely confirm IgE-dependent sensitization. Aim : Investigation of the incidence of IgE-dependent FA and airborne allergy in AD patients. Clinical evaluation of AD patients considering the coexistence of IgE-related sensitization to environmental allergens. Material and methods: Hundred and two patients with AD, controls: 20 patients with allergic rhinitis (AR), 20 healthy volunteers. In AD patients > 4 years skin prick tests (SPT) with airborne allergens; depending on age, SAFT, APT or SPT with food allergens. Evaluation of disease extent and severity with two scores: SCORAD and W-AZS. Results : Symptoms of FA were reported by 68%, while IgE-dependent FA was diagnosed exclusively in children < 5 years (16% of the population); airborne allergy in 63% of the examined population. Extrinsic phenotype of AD (eAD) was observed in 71%, intrinsic (iAD) in 29%. Increased W-AZS was observed in AD patients with FA compared with the rest of the AD population (p = 0.006), eAD with airborne allergy (p = 0.041) and iAD (p = 0). Increased SCORAD was observed in AD patients with FA compared to the rest of the AD group (p = 0.005) and iAD (p = 0). Conclusions : A significant difference was observed in the incidence of self-reported symptoms of FA between the AD group and IgE-dependent FA, while airborne allergy was observed in the majority of patients. Statistically higher scores of W-AZS and SCORAD index indicate that food allergens may play some role in the development of AD in children.